The Mechanical Behavior During (De)lithiation of Coated Silicon Nanoparticles as Anode Material for Lithium‐Ion Batteries Studied By In Situ Transmission Electron Microscopy. Issue 8 (29th June 2016) - Van Havenbergh, Kristof; Turner, Stuart; Marx, Nicolas; Van Tendeloo, Gustaaf
Abstract: One approach to cope with the continuous irreversible capacity loss in Si‐based electrodes, attributed to lithiation‐induced volume changes and the formation of a solid–electrolyte interface (SEI), is by coating silicon nanoparticles. A coating can improve the conductivity of the electrode, form a chemical shield against the electrolyte, or provide mechanical confinement to reduce the volume increase. The influence of such a coating on the mechanical behavior of silicon nanoparticles during Li insertion and Li extraction was investigated by in situ transmission electron microscopy. The type of coating was shown to influence the size of the unreacted core that remains after reaction of silicon with lithium. Furthermore, two mechanisms to relieve the stress generated during volume expansion are reported: the initiation of cracks and the formation of nanovoids. Both result in a full reaction of the silicon nanoparticles, whereas with the formation of cracks, additional surface area is created, on which an SEI can be formed. Abstract : A Si of relief : The influence of volume changes, intrinsic to the reaction of Li with Si, on several applied coatings is evaluated with in situ transmission electron microscopy. Two mechanisms of stress relief are reported: the initiation of cracks and the formation of nanovoids. When stress relief occurs, an unreacted, crystalline core remains in the silicon nanoparticles, of which the size is dependent on the type of coating.